What do they know? Is Climate Change Education Necessary in Primary Schools in Serbia - Leščešen, Igor; Basarin, Biljana; Vujičić, Miroslav (Geographica Pannonica, 2024)
Climate change is a global crisis exacerbated by human activity and a matter of urgent con- cern. There is a significant knowledge gap among primary school students in Serbia, as the topic of climate change is barely covered in the curriculum. This study examines their aware- ness, knowledge and attitudes. Of the participants, 96.6% are aware of climate change, but their knowledge and attitudes vary considerably. Some 80.10% expect climate change to have a significant impact on humans through floods (90%), droughts and tempera- ture increases (85% each). Further results show that schools are a key source of information (35.10%), followed by television (30.10%) and the internet (14.90%). In summary, this study highlights the need for comprehensive, multidisciplinary climate education to address dif- ferent levels of awareness, encourage informed and proactive responses and engage young voices in discussions about climate change.